Adjustment in Indonesia’s Exports to the United States: A Perspective from the Partial Adjustment Model - Hanif Nindy Asyifa (Advances: Jurnal Ekonomi & Bisnis, 2026)
Purpose: This study analyzes the short-run and long-run adjustment dynamics of Indonesia’s export value to the United States by examining the effects of the exchange rate, Industrial Production Index (IPI), COVID-19, and geopolitical conflicts across several commodity groups. Research Method: Monthly time-series data from 2018–2025 obtained from the International Trade Center (ITC), Bank Indonesia, and Badan Pusat Statistik (BPS) are analyzed using the Partial Adjustment Model (PAM) and Ordinary Least Squares (OLS). Lagged export variables are included to capture dynamic adjustment processes, supported by classical assumptions and diagnostic tests. Results and Discussion: The findings show that the exchange rate has no significant short-run effect on export value, whereas IPI has a positive and significant effect on all commodity groups. COVID-19 and geopolitical conflicts also demonstrate positive effects with varying significance levels. The results further confirm the existence of partial adjustment mechanisms with different adjustment speeds across commodities. Implications: The study suggests that export policies should prioritize industrial strengthening and adaptive sector-based trade strategies under global uncertainty. Originality: This study integrates domestic macroeconomic factors and global shocks within a commodity-based PAM framework.